CONFIGURAÇÃO DE IMAGENS: UM ESTUDO COM SERVIÇOS DE FISIOTERAPIA - Gabriel Sperandio Milan (GESTÃO.Org : Revista Eletrônica de Gestão Organizacional, 2008)
The mental images constitute one of the most important intellectual materials of the man, influencing and directing his behavior. Finding support in the TCI (Technique of the Configuration of Images), this research makes a deep study in the understanding of the configuration of images, using the context of the physiotherapy services of a Health Plan. First of all, it was identified the attributes related to the functional, symbolic, cognitive and emotional elements of the physiotherapy service image for the three kinds of patients (post-operated, neurological and chronic ones). After, such attributes were organized according to their proximity to the central idea of the service, presenting also, the MCISs (Maps of the Service Configuration of Images), a tool that is able to synthesize the results of the research and work as a support to the process of taking decisions on the administration of the services. The results suggest that the used technique constitutes a great alternative for the management of images and for the control of the performance of a service.